Guidelines in Selecting Enterprise Resource Planning System for Human Resource Management: The Case Study of OGAS Solutions (Thailand) Company Limited - Singsatorn, Prapapan; Chansom, Nakamol (Rajapark Journal, 2021)
The objectives of this research are 1) to study the current situation and problems in human resource work of OGAS Solutions (Thailand) Co., Ltd. and the efficiency of the ERP system to solve the human resource problems of OGAS Solutions (Thailand) Co., Ltd., 2) to study factors affecting the decision to select ERP software of OGAS Solutions (Thailand) Co., Ltd., and 3) to provide appropriate guidelines for decision making in selecting to use ERP software regarding human resource management of OGAS Solutions (Thailand) Co., Ltd. This research is qualitative. The population consisted of 13 people who were divided according to their roles in providing information based on the research objectives, comprising supervisors, operation staff, and senior executives with decision-making authority. The research method was conducted using the In-Depth Interview. The results revealed that 1) The problem of the human resource of OGAS Solutions (Thailand) Co., Ltd, there was no independent human resource staff; however, the payroll management software could be used to solve the problem of human resource operation at the company. 2) The factors affecting the decision on the selection of ERP system software of OGAS Solutions (Thailand) Co., Ltd., were the system’s efficiency, price, and company policy. 3) The appropriate guidelines in selecting an ERP system are to establish human resource management’s objectives and policies, to hire personnel of human resources and to utilize the ERP system for human resource management.